A novel indeno[1, 2-b]pyridinone derivative, a DNA intercalative human topoisomerase IIα catalytic inhibitor, for caspase 3-independent anticancer activity. Issue 51 (12th June 2017) - Jeon, K. H.; Park, C.; Kadayat, T. M.; Shrestha, A.; Lee, E. S.; Kwon, Y.
Abstract : A novel 2-(furan-2-yl)-4-(pyridin-2-yl)-5 H -indeno[1, 2- b ]pyridin-5-one (TI-1-190) was synthesized using a simple microwave-assisted method and its mode of action was systematically characterized. Abstract : A novel 2-(furan-2-yl)-4-(pyridin-2-yl)-5 H -indeno[1, 2- b ]pyridin-5-one (TI-1-190) was synthesized using a simple microwave-assisted method and its mode of action was systematically characterized. It is a DNA intercalative human topoisomerase IIα catalytic inhibitor with much stronger activity and less DNA toxicity than etoposide, a topoisomerase II poison. TI-1-190 displays caspase 3-independent anticancer activity, unlike etoposide.